THE EFFECT OF IRON SUPPLEMENTATION AND OTHER SCHOOL-BASED SUPPORT ON ANEMIA STATUS IN ADOLESCENTS: A SYSTEMATIC LITERATURE REVIEW - Amani, Zahiroh; Sebayang, Susy Katikana (UNIVERSITAS AIRLANGGA, 2024)
Background: Anmia among adolescent girls is still problematic. The 2018 RISKESDAS Indonesia survey revealed that anemia among pregnant women was linked to the high prevalence of anemia among adolescents (25%) and women of reproductive age (17%). School support is considered important to help overcome the problem of anemia among adolescent girls. This research aims to assess the effectiveness of school support in providing iron supplements and other support for anemia status in adolescents. Method: This was Systematic Literature Review of publications found on Google Scholar and Pubmed databases using the following inclusion criteria: published in Indonesian or international journals between 2018 – 2023 and written in Bahasa Indonesia or English. The article search utilized the following keywords on Google Scholar: